Takhrij and Syarah Hadith of Chemistry: The Bad Effects of Wearing Gold on Men's Health - Ervina Surya Aini; Nurul Ashfiya Farhanah; Gina Giftia Azmiana Delilah; Neng Hannah; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2021)
The purpose of this study to discuss the hadith of the Prophet (s) concerning the use of gold jewelry for men. This method is qualitative through takhrij approach and hadith syarah with chemical analysis. The result and discussion of this study is the danger of wearing gold for men. The conclusion of this study is takhrij and syarah hadith of the Prophet about the bad effects of wearing gold on men's health.